Kesiapsiagaan Masyarakat Di Desa Dukun Kecamatan Dukun Kabupaten Magelang Kawasan Resiko Bencana ( KRB ) III dalam Penanggulangan Bencana - Margono Margono; M Khoirul Amin; Retna Tri Astuti (Fakultas Ilmu Kesehatan, 2019)
Abstract Introduction: Magelang Regency is one of the areas on the slopes of Merapi Mountain with the greatest disaster risk is volcanic eruptions. Dukun Village is one of the volcanic disaster-prone areas located approximately 8 km from the top of the mountain and included as Disaster Risk Area III in Magelang Regency. In the eruption on 2010 most of the Dukun community evacuated to other districts avoiding the hot clouds. The volcano in Magelang was on alert status from May 21, 2018. Within a period of 1.5 years, several volcanoes emitted volcanic ash and earthquakes. Under these circumstances, the risk of disaster in the community is very high, especially those in the Disaster Risk Area III of Merapi Mountain. Community based disaster management needs to be improved, especially in preparation for disaster preparedness. Method: the type of this research is descriptive quantitative, with a field survey analysis method using a questionnaire about the community preparedness at Dukun Village in Disaster Risk Area III dealing with disasters. Results: The results showed the community analysis of disaster risk in the Dukun village was a volcanic eruption with a percentage of 96% of the community, source of information obtained by the community about the disaster 89% showed from village officials, as many as 74% of families had participated in the socialization of the disaster but the majority were only the family heads, as much as 66% have sought disaster risk reduction and as many as 33.5% of the community if there is a plan to evacuate siblings. Family preparedness in preparing first aid kits was still very low. Conclusion: The Dukun Village community has realized that being in a disaster-prone area, at present the majority of families have participated in preparedness socialization but in disaster risk reduction and preparation is still lacking.